Financial literacy, digital transformation adoption, and their significance to the MSMEs performance in Bandung city - Dwi Rahmawati; Abdurrahman Rahim Thaha; Agus Priyanto (Universitas Tarumanagara, 2023)
Financial and digital literacy has been recognized as a crucial information resource for financial decision-making, but the impact of MSME’s financial and digital literacy on sustainability has received little attention. This study intends to examine the growth of MSME’s financial knowledge and technology adoption-related obstacles. A solid business foundation, which is sorely needed, can be created by training MSMEs about financial and digital literacy in a systematic, integrated, and sustainable way. This study is quantitative research considering it employs descriptive statistical analysis of numerical data, especially the partial least square method, to examine the impact of financial and digital literacy on the performance of MSMEs. The 237 respondents in Bandung who participated in a self-administered survey were used to get the data during the third quarter of 2022. The study proved that the performance of entrepreneurs was statistically influenced by financial literacy and digital transformation adoption. Comparing the two major attributes, digital transformation has a higher score in impacting the MSME’s performance. Bandung is one of the key pillars of the local economy, especially MSMEs where performance is affected majorly by digital transformation adoption. Literasi keuangan dan digital telah diakui sebagai sumber informasi penting untuk pengambilan keputusan keuangan, tetapi dampak literasi keuangan dan digital UMKM terhadap keberlanjutan kurang mendapat perhatian. Penelitian ini bermaksud untuk mengkaji pertumbuhan pengetahuan keuangan UMKM dan hambatan terkait adopsi teknologi. Fondasi bisnis yang kokoh, yang sangat dibutuhkan, dapat diciptakan dengan melatih UMKM tentang literasi keuangan dan digital secara sistematis, terintegrasi, dan berkelanjutan. Penelitian ini merupakan penelitian kuantitatif mengingat menggunakan analisis statistik deskriptif data numerik, khususnya metode Partial Least Square, untuk mengkaji dampak literasi keuangan dan digital terhadap kinerja UMKM. Ke-237 responden di Bandung yang mengikuti survei swakelola digunakan untuk mendapatkan data selama kuartal III-2022. Studi ini membuktikan bahwa kinerja wirausahawan secara statistik dipengaruhi oleh literasi keuangan dan adopsi transformasi digital. Membandingkan dua atribut utama, transformasi digital memiliki skor yang lebih tinggi dalam mempengaruhi kinerja UMKM. Bandung merupakan salah satu pilar utama perekonomian lokal, khususnya UMKM dimana kinerjanya sangat dipengaruhi oleh adopsi transformasi digital.